Trigeminal Nerve Stimulation for Major Depressive Disorder: An Updated Systematic Review - Trevizol, Alisson Paulino [UNIFESP] (2017)
Context: Trigeminal nerve stimulation (TNS) is a promising non-invasive brain stimulation intervention. The TNS has been proposed for major depressive disorder (MDD) with auspicious results. The aim of this study was to review the literature on TNS for MDD. Evidence Acquisition: Systematic review, using MEDLINE and EMBASE, of first articles available until 22nd of April 2016. Results: We included seven studies